Influencia del TiO2 y Al2O3 sobre las propiedades eléctricas y microestructurales de cerámicas de SnO2 obtenidas por el método Pechini - Mosquera, A. (2008)
Tin oxide has wakened up great scientific and technological interest for its potential use in varistors production and as gas sensor. In order to improve the microstructural and electrical properties in SnO varistor ceramics, the influence of differents dopants used, like TiO2 and Al2O3, is under research. The effect of TiO2 and Al2O3 on the properties of Sn-Co-Nb varistor Systems obtained by the Pechini method has been investigated in this work. Characterization of synthesized raw material was performed by X-Ray Diffraction (XRD) and Scanning Electronic Microscopy (SEM). The microstructural and electrical characterization of sintered samples show that the TiO2 favors the grain growth and the Al2O3, contributes to the decrease it, effect that is manifested in the Sn-Co-Nb varistor systems. Breakdown field increase up to 6300V/cm with increasing Al2O3 content and non-linear coefficients with α=22 were obtained.